Pre-Testing Muhammadiyah COVID-19 Guidelines in Jakarta Province - Handayani, Sarah; Khoiriyah, Rizqiyani (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
Muhammadiyah, being one of the religious-based organizations, has its affiliated members comprising 14,9% of the general Indonesian population. The Muhammadiyah Central Board declared an ad-hoc group called the Muhammadiyah COVID-19 Command Centre (MCCC) to combat COVID-19. Among the used media were the third COVID-19 guidelines publications by the MCCC. This study aimed to determine the Muhammadiyah members’ understanding of the COVID-19 Revision III Guidelines based on their consistency, clarity, relevance, credibility, and interest. This research was a descriptive qualitative type of study. The eleven informants who participated in this study, determined by purposive sampling, were Muhammadiyah members who lived and worked in the Jakarta. These Informants consisted of various professions, including health workers, teachers, district board members, nurses, drivers, traders, housewives, and students. Data collection was by online focus group discussions through the zoom cloud meetings platform. Informants discussed the five aspects of the guideline which included consistency, clarity, relevancy, credibility and interest. The contents of the guideline were found to be consistent with other similar guidelines published by the Ministry of Health (MOH). In addition, being affiliated members of the Muhammadiyah group, informants felt more comfortable trusting the Muhammadiyah-published COVID-19 guidelines. From the clarity and relevance aspect, the informants had positive perspectives on the guidelines. The design of the published guidelines attracted their interest in reading, implementing, and sharing the guidelines with others. However, the guideline did not contain the names of its drafting team nor the introduction by the Central Board leadership. It would have been a very important strategy in strengthening the credibility of the media published by the MCCC. The MCCC needed more enticing plans and methods in the dissemination of its online or printed media to the population. For online media, the published number of pages should be fixed to a less readable number.